Frequency of Intestinal Tuberculosis in Patients of Intestinal Perforation Presenting in Surgical Emergency (Medical Forum Monthly, 2024)
Objective: To determine the frequency of intestinal tuberculosis in patients of intestinal perforation presenting in surgical emergency.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Surgery, Nishter Hospital Multan from January 2016 to June 2016.Materials and Methods: Total 83 patients having age from 20-50 years, either male or female with intestinal perforation were selected. Laparotomy was performed in all selected patients and tissue was sent to laboratory for histopathology.Results: Mean age of the age range was 20-50 years with mean age 33.88±9.82 years. Out of 83 patients, intestinal tuberculosis was found in 20 (24%) patients. In age group 36-50 years out of 39 (46.99%) patients, intestinal tuberculosis was found in 10 (25.64%) patients. No association (P = 0.800) between age and intestinal tuberculosis was found. Total 40 (48.19%) patients were malnourished and intestinal tuberculosis was found in 16 (40%) patients. Total 43 (51.81%) patients were properly nourished and intestinal tuberculosis was noted in 4 (9.30%) patients. Significantly (0.001) higher rate of intestinal tuberculosis was noted in malnourished patients as compared to properly nourished patients.Conclusion: Acute abdominal condition is one of the most common emergencies in trauma room, and acute abdominal tuberculosis is one of common causes of acute abdomen in endemic areas as Intestinal tuberculosis is a common extra-pulmonary Manifestation of tuberculosis. Its incidence is increasing in urban and rural areas due to poverty, under nutrition and overcrowding, Intestinal and abdominal tuberculosis is a systemic disease.